Inhibition of a Golgi Complex Lysophospholipid Acyltransferase Induces Membrane Tubule Formation and Retrograde Trafficking - Drecktrah, Daniel (The American Society for Cell Biology, 2003)
Recent studies have suggested that formation of Golgi membrane tubules involves the generation of membrane-associated lysophospholipids by a cytoplasmic Ca(2)(+)-independent phospholipase A(2) (PLA(2)). Herein, we provide additional support for this idea by showing that inhibition of lysophospholipid reacylation by a novel Golgi-associated lysophosphatidylcholine acyltransferase (LPAT) induces the rapid tubulation of Golgi membranes, leading in their retrograde movement to the endoplasmic reticulum. Inhibition of the Golgi LPAT was achieved by 2,2-dimethyl-N-(2,4,6-trimethoxyphenyl)dodecanamide (CI-976), a previously characterized antagonist of acyl-CoA cholesterol acyltransferase. The effect of CI-976 was similar to that of brefeldin A, except that the coatomer subunit β-COP remained on Golgi-derived membrane tubules. CI-976 also enhanced the cytosol-dependent formation of tubules from Golgi complexes in vitro and increased the levels of lysophosphatidylcholine in Golgi membranes. Moreover, preincubation of cells with PLA(2) antagonists inhibited the ability of CI-976 to induce tubules. These results suggest that Golgi membrane tubule formation can result from increasing the content of lysophospholipids in membranes, either by stimulation of a PLA(2) or by inhibition of an LPAT. These two opposing enzyme activities may help to coordinately regulate Golgi membrane shape and tubule formation.